Astaxanthin intake alleviates gouty arthritis in patients and rats by modulating the levels of various inflammatory markers. (December 2021) - Zhang, Lin; Chen, Hao; Ding, Kaiyue; He, Shiyong; Li, Guangxing; Qu, Jialin; Qiao, Yanling; Zhang, Liu; Sui, Xue; Fan, Chao; Wen, Jin; Wu, Wenzhong; et al.
Graphical abstract: Highlights: The effects of astaxanthin on gout were observed in a randomized controlled trial. Astaxanthin has a lowering effect on the index of gout arthritis. Astaxanthin combined with western medicine may be an alternative method for gout. Contributing a rationale for astaxanthin as a dietary supplement to assist in gout. Abstract: Gout is a form of arthritis caused by hyperuricemia that can significantly affect a patient's quality of life. Here, we investigated the therapeutic effects of astaxanthin, a carotenoid with strong anti-inflammatory and antioxidant properties, on gout. The results of animal experiments showed that in terms of animal serological indicators, astaxanthin has the same effect as colchicine in treating gouty arthritis. The outcomes of clinical trials showed that the astaxanthin at 8 mg/d combined with celecoxib at 100 mg/d worked better than celecoxib at 200 mg/d according to ESR and UA, and according to CRP, the effect was comparable. The molecular mechanisms underlying the therapeutic effects of astaxanthin included inhibition of COX-2 and anti-inflammation and anti-oxidation. Collectively, astaxanthin ameliorated gout in rats' model of gouty arthritis and clinical trials suggesting that it has potential as a dietary supplement to assist in the treatment of gouty arthritis.